Implementasi Metode Distribution Requirements Planning (DRP) Untuk Mendukung Strategi Supply Chain pada PT Yudhistira Cabang Samarinda - Moh Syahroni; Anis Rachma Utary; Maryam Nadir (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2017)
The results of applying the method of Distribution Requirements Planning (DRP) in the period from April 2017 s / d September 2017 having a stable distribution of significant visible Projected On Hand at the end of the Book of Mathematics in the Region Smd 42 exp, Mathematics Area Bpn 39 exp, Mathematics in Region of Btg 37 exp, Indonesian Territory Smd, 41 exp, Indonesian Territory Bpn 41 exp, Indonesian Province Btg 40 exp, Natural Sciences in the region Smd 40 exp, Natural Sciences in the region Bpn 39 exp, Natural Sciences area 39 exp Btg, which means there are no vacancies or excess Projected on Hand is determined by the company, which is 84 exp. Supply chain in PT. Yudhistira Cab. Samarinda shows that the title of the book Mathematics minimum cost in Bontang Area Rp. 589,095. Indonesian with cost Rp. 620,730. Natural Sciences Rp. 643,455.Keyword:  Distribution  Requirements Planning (DRP) end supply chain